Embolization of arteriovenous malformations of the temporal lobe via the anterior choroidal artery. - Hodes, J E; Aymard, A; Casasco, A; Rüfenacht, D; Reizine, D; Merland, J J (American Journal of Neuroradiology, 1991)
The indications, technique, and results of embolization of arteriovenous malformations with liquid adhesive agents delivered through the anterior choroidal artery are reported. Arteriovenous malformations of the temporal lobe were found in four patients with intracerebral bleeding and two with intractable epilepsy. In five of the six, the dominant arterial feeder was the anterior choroidal artery. All patients underwent superselective catheterization of the anterior choroidal artery and embolization of the arteriovenous malformation. Complications related to the anterior choroidal artery embolization developed after embolization in one patient, after which we changed our technique of embolizing arteriovenous malformations via this artery. A thorough understanding of the functional anatomic structures supplied by each segment of the artery is important. Guidelines for safe catheterization and embolization are given. Embolization of arteriovenous malformations fed predominantly by the anterior choroidal artery is difficult and dangerous. An understanding of the functional anatomy of this artery and proper technique can enable successful embolization of arteriovenous malformations via this route.